Anglicism in Speech of Emmanuel Macron and François Hollande - Marice; Isda Pramuniati; Mahriyuni; William Hutapea (Jurnal Pedagogi dan Pembelajaran, 2023)
Lexical Anglicism is the use of English terms or expressions. Phonetic Anglicism is a mispronunciation, such as pronouncing zoo as [zo]. This study aims to analyze how Emmanuel Macron and François Hollande use Anglicism in their speeches. A loanword that is English in the form, including spelling, sound, and morphology — that's what we call an "Anglicism". The main topic of this research is phonetic and lexical Anglicism. The research methodology combines qualitative descriptive analysis with content analysis. According to sources, content analysis is made possible by recording, concluding and analyzing the English speeches of Francois Hollande and Emmanuel Macron, which were uploaded on YouTube. The main topic of this research is phonetic and lexical Anglicism. The next step after collecting the data is to analyze it. The study results using anglicisms in 5 videos of Emmanuel Macron's speeches on YouTube 32 data. In comparison, the use of anglicisms in 5 videos of François Hollande's speeches on YouTube is lacking, namely 9 data. The speeches of Macron and Hollande contain 41 anglicisms, of which the words of anglicisms can be classified into five categories: nouns (28), verbs (3), abbreviations (7), adjectives (2) and interjections (1).